2010
DOI: 10.1348/014466509x415735
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating the cry of pain model of suicidality: Testing a psychological model in a sample of first‐time and repeat self‐harm patients

Abstract: Objectives. Few studies have specifically tested the Cry of Pain model (Williams, 2001). This model conceptualises suicidal behaviour as a behavioural response to a stressful situation which has three components: defeat, no escape potential, and no rescue. In addition, the model specifies a mediating role for entrapment on the defeatsuicidal ideation relationship, and a moderating role for rescue factors on the entrapment-suicidal ideation relationship. This is the first study to investigate the utility of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 24 publications
16
101
0
5
Order By: Relevance
“…There is growing empirical evidence for the central tenets of the arrested flight model of suicidal behaviour (O'Connor, 2003;Rasmussen, Fraser, Gotz, MacHale, Mackie, et al, 2010;. In a casecontrol study, O'Connor (2003) found that the arrested flight variables (high inescapability, high defeat, and low social support) significantly discriminated between self-harm patients and controls.…”
Section: Conceptual and Empirical Rationale For Imvmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing empirical evidence for the central tenets of the arrested flight model of suicidal behaviour (O'Connor, 2003;Rasmussen, Fraser, Gotz, MacHale, Mackie, et al, 2010;. In a casecontrol study, O'Connor (2003) found that the arrested flight variables (high inescapability, high defeat, and low social support) significantly discriminated between self-harm patients and controls.…”
Section: Conceptual and Empirical Rationale For Imvmentioning
confidence: 99%
“…Moreover, in the multivariate analyses none of the clinical variables (anxiety, depression, hopelessness) was a statistically significant predictor when considered alongside the arrested flight variables. In a more recent case-control study, Rasmussen et al (2010) compared three groups of patients (first-time self-harm patients versus repeat self-harm patients versus hospital controls) on the arrested flight variables and found that the three groups differed along each of these constructs in the predicted directions (see Figure 11.2). Thus, repeat self-harm patients reported significantly higher levels of entrapment than first-time self-harm patients and hospital controls.…”
Section: Conceptual and Empirical Rationale For Imvmentioning
confidence: 99%
“…Consequently, if an individual perceives no escape or rescue from the situation, suicidal ideation emerges. More recently, defeat and entrapment have been shown to be important factors in understanding suicidal thoughts and actions [25] and self-harm [26] cross-sectionally and over time [27,28].…”
Section: How Are Social Comparisons Related To Suicidal Outcomes?mentioning
confidence: 99%
“…Social withdrawal represents a perilous risk process for exceeding the threshold to suicidal behavior. On the one hand, it fosters a cognitive and emotional narrowing, in which positive future-oriented thoughts are hardly accessible (Rasmussen et al, 2010). On the other hand, through social withdrawal, the person (consciously or non-consciously) creates "favorable" conditions to be able to attempt suicide uninterruptedly.…”
Section: Discussionmentioning
confidence: 99%